IMPACT OF DIGITAL MARKETING ON ONLINE PURCHASE INTENTION: MEDIATION EFFECT OF CUSTOMER RELATIONSHIP MANAGEMENT AND RESPONSIVE CUSTOMER ORIENTATION OF CHINESE CUSTOMERS - Zhibin Chen; Arti Pandey (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
Abstract: The high growth of internet and the usage of smartphones has transformed consumerism and business approaches in the digital economy of China. This paper examines the impact of digital marketing on online purchase intention focusing on mediating variables Customer Relationship Management (CRM) and Responsive Customer Orientation (RCO). Based on the Theory of Planned Behavior (TPB), a structured questionnaire was sent to the online consumers in Shenzhen and 400 valid responses were obtained. The strength of the measurement model was also proved during reliability and validity tests and multiple regression analysis revealed that digital marketing has a positive impact on both CRM and RCO which positively influence purchase intention. Mediation analysis also showed that CRM has a greater mediating impact than RCO. These results indicate that digital marketing performance is not limited by technological coverage, but it depends on the practices that are customer-centric and can help build trust, responsiveness, and loyalty. The research has added value to TPB applications in digital marketing, offered managerial implications to enhance CRM and responsiveness strategies and has given future research directions on the utilization of a broader sample, longitudinal designs and inclusion of other constructs like brand trust and customer satisfaction.